Ethnomethodology of Agricultural Zakat: The Problematic of Nisab Calculation in Lima Puluh Kota Regency - muhammad yusuf; Marnala Sitinjak; Masril masril; Ramadahniel Islami; Kris Permana Putra (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to examine the application of the ethnomathematics method in calculating the nisab and the rate of zakat on rice among farming communities. It also seeks to determine the actual nisab and zakat rate applied by farmers, as well as to explore the Islamic economic perspective on the use of ethnomathematics in calculating the nisab and zakat rate on rice in the farming community of Lima Puluh Kota Regency. This research is a field study using a qualitative approach, with data collected through in-depth interviews, observations, and documentation. The respondents were determined using the snowball sampling technique, involving 16 informants. The study was conducted in Lima Puluh Kota Regency, specifically in Pangkalan Koto Baru District, and the data were analyzed descriptively. The results of the study indicate that farmers in Lima Puluh Kota Regency use the “kaleng” (can) as a unit of measurement in determining the nisab, where 100 kaleng is considered the nisab, and the zakat rate is 10 kaleng. The ethnomathematical concept found shows that 1 kaleng of rice equals 12 kilograms of paddy, which produces 7 kilograms of milled rice. This demonstrates a difference between the ethnomathematical calculation used by farmers and the fiqh-based zakat rulings established by the majority of scholars.According to the standard zakat law, the nisab for rice zakat is 1,119.242 kilograms of paddy or approximately 93.270 kaleng, and the zakat rate should be 5% because the crops are irrigated and require planting costs. The discrepancy between the farmers’ calculation of nisab and zakat rate, which exceeds the established fiqh standards, may lead to delays in zakat collection and distribution to the eight asnaf (eligible recipients). Such delays may also hinder the welfare of the asnaf who depend on these funds